SEJARAH DAN MAKNA RUMAH ADAT DI DESA MORAMAM, KECAMATAN ALORBARAT DAYA KABUPATEN ALOR - Matias Lau mau Pating; Muhamad Songge; Onarita Lanoni, Uriana Mabileti, Marsia Alomau, Martha Lanmai, Jennie Tunliu, Paulina Lambila, Halen (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2025)
This study examines the uniqueness of the history and meaning of traditional houses in Moramam Village, Alor Barat Daya District, Alor Regency. The research method used is a qualitative method with an ethnographic approach, involving direct observation, in-depth interviews with traditional elders, and related literature studies. The results showed that the traditional house in Moramam Village has a distinctive architecture that reflects the cultural identity of the Alor community. The structure of the building, which consists of strong wooden pillars, symbolises the resilience of the community, while the conical roof reflects the harmonious relationship between humans, nature and ancestors. In addition, the traditional house also functions as a place for traditional ceremonies and community deliberations. Thus, the traditional house in Moramam Village is not just a place to live, but also a centre of social and cultural life that has been passed down from generation to generation. This research is expected to be a reference in the effort to preserve traditional houses as part of the national cultural wealth. In addition, this research also reveals various challenges in the preservation of traditional houses, including changes in people's lifestyles, the influence of modernisation, and lack of attention from related parties. Therefore, collaborative efforts between the community, government, and academics are needed to maintain the sustainability of traditional houses as a local cultural identity.